The Comprehensive Systematic Review of Association of the HLA-B27 antigen to the development of ankylosing spondylitis - Clareta Vero Patricia Widya; Devina Adelina Wijaya (The International Journal of Medical Science and Health Research, 2026)
Introduction: Ankylosing Spondylitis (AS) is a chronic inflammatory arthritis primarily affecting the axial skeleton, with a well-established but complex genetic association with the Human Leukocyte Antigen B27 (HLA-B27). Despite decades of research, the precise mechanisms, the differential roles of HLA-B27 subtypes, and the influence of geographic and genetic modifiers remain areas of active investigation (Reveille, 2006). Methods: This comprehensive systematic review synthesized evidence from 80 studies, including case-control studies, cohort studies, and meta-analyses. A stringent screening process was applied, focusing on studies with defined AS diagnostic criteria, confirmed HLA-B27 testing, comparison groups, and reported statistical measures of association. Data extraction covered study design, population characteristics, HLA-B27 testing methods, AS definitions, association results (odds ratios, relative risks), HLA-B27 prevalence, subtype analyses, epistatic interactions, and clinical phenotype correlations. Results: The analysis confirmed an exceptionally strong association between HLA-B27 and AS, with relative risks estimated between 50 and 100 for carriers. However, significant heterogeneity exists. HLA-B27 prevalence in AS patients varies geographically, from ~90% in Caucasian and Asian populations to as low as 26.2% in some Middle Eastern countries. Critical nuances emerged: specific subtypes confer differential risk (e.g., B2704 is a risk factor, while B2706 and B*2707 are protective), and powerful epistatic interactions were identified, particularly with HLA-B60 (RR up to 342) and ERAP1 polymorphisms. Clinically, HLA-B27 positivity is associated with earlier disease onset, better response to biologic therapies, and shorter diagnostic delays, but a lower-than-expected diagnostic likelihood ratio (LR+ 2.7) (A. D. Vieira Bento Silva et al., 2023). Discussion: The findings underscore that HLA-B27 is a necessary but insufficient factor for AS pathogenesis. The disease risk is modulated by a complex interplay of specific HLA-B27 subtypes, co-inherited genetic factors (epistasis), and population-specific genetic backgrounds. This complexity explains why only 1-5% of HLA-B27 carriers develop AS and accounts for the wide geographic variation in disease association strength. Conclusion: HLA-B27 remains the paramount genetic risk factor for AS, but its clinical and pathogenic interpretation must account for subtype variation, epistatic interactions, and ethnic background. Future research should prioritize elucidating the molecular mechanisms of protective subtypes and integrating polygenic risk scores with HLA status for improved diagnosis, prognosis, and personalized treatment strategies.